2022
DOI: 10.1186/s12884-022-04679-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with caesarean section in Rwanda: a trend analysis of Rwanda demographic and health survey 2000 to 2019–20

Abstract: Background Caesarean section (CS) is an important medical intervention for reducing the risk of poor perinatal outcomes. However, CS trends in sub-Saharan Africa (SSA) continue to increase yet maternal and neonatal mortality and morbidity remain high. Rwanda, like many other countries in SSA, has shown an increasing trend in the use of CS. This study assessed the trends and factors associated with CS delivery in Rwanda over the past two decades. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 53 publications
5
31
0
Order By: Relevance
“…Finally, we found that the more children women had, the less likely they were to undergo CS delivery. Our results align with other studies conducted in Rwanda [ 6 ], Kenya [ 39 ], and Ethiopia [ 24 , 77 ]. A possible explanation is that women who had 5 or more children had previously given birth successfully or experienced fewer complications requiring CS [ 24 , 69 , 78 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, we found that the more children women had, the less likely they were to undergo CS delivery. Our results align with other studies conducted in Rwanda [ 6 ], Kenya [ 39 ], and Ethiopia [ 24 , 77 ]. A possible explanation is that women who had 5 or more children had previously given birth successfully or experienced fewer complications requiring CS [ 24 , 69 , 78 ].…”
Section: Discussionsupporting
confidence: 92%
“…Children with big size at birth had higher odds of CS compared to those with an average size. Former studies [ 6 , 55 ] affirmed this association between size of child at birth and CS. Big babies often have difficulties during deliveries (birth complications) due to insufficient passage and prolonged labor [ 6 , 56 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7 As shown study carried out in Kigali City, Rwanda the rate of CS significantly increased. 8 Sub-Saharan Africa (SSA); although the mean Cesarean delivery rate in SSA (5%) was shown the lowest rise, this rate is not representative of all regions. 9 Nationally; studies on cesarean delivery conducted in different settings showed substantial variations across administrative regions and places of delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, such as Thailand, the rate of cesarean section in private care is almost ten-fold higher than in the public sector. In others, such as Rwanda, it is four times higher, and in India it is three times higher [ 6 , 7 ]. The situation is even more alarming in Bangladesh, where among the 50% of deliveries that take place in medical facilities, almost two-thirds are in private care facilities, where the CS ratio is 83% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%